Pelaksanaan Perlindungan Hukum Terhadap Perempuan Sebagai Saksi Korban Kekerasan Dalam Rumah Tangga - Andrie Eka Putra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
Violence against women in general is a problem experienced by many women, especially if the violence occurs in the household, because the problem is still considered taboo and is still considered a family problem that is resolved kinship. This shows that there are still many female victims of domestic violence that keep their mouths shut and keep these problems tightly. The formulations of the problems raised are 1) What are the factors causing violence in the household, 2) How is the implementation of the law against women as witnesses of domestic violence in Denpasar District Court. The type of research used is the type of empirical research. The results of the discussion of this study are the factors that cause domestic violence to occur due to the lack of communication between husband and wife in the family which is a determinant of family harmony and the implementation of legal protection for women as witnesses of victims of domestic violence in Denpasar District Court. run effectively as stipulated in the legal provisions. So that law enforcement officers can resolve cases of domestic violence properly so that they can provide protection to women as victims of domestic violence.